2019
DOI: 10.1002/ardp.201900209
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and antimicrobial activity of some new N‐aryl‐N’‐(2‐oxoindolin‐3‐ylidene)‐benzohydrazonamides

Abstract: A green approach was developed for synthesizing a series of (isatin‐3‐ylidene)‐hydrazonamides 3a–j from the reaction between isatin, (isatin‐3‐ylidene)malononitrile, or 2‐cyano‐2‐(2‐isatin‐3‐ylidene)acetate and benzohydrazonamide in ethyl acetate solutions at ambient temperature. The structures of the new compounds were confirmed on the basis of spectral data. In this eco‐friendly medium, a variety of (isatin‐3‐ylidene)hydrazonamides were obtained free of catalyst in good to excellent yields. All the synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…In 2019, Gomaa et al [ 72 ] reported the synthesis and in vitro antimicrobial potential of N-aryl-N′-(2-oxoindolin-3-ylidene)-benzohydrazonamides ( 50a – j ) against B. cereus , S. aureus (Gram-positive), and E. coli , P. aeruginosa , and S. marcescens strains using the agar disc diffusion method. The research group emphasized that compounds 50b and 50d show the most promising activity towards S. aureus when compared to the standard drug ciprofloxacin, while the majority of analogues displayed broad-spectrum antibacterial potential against all tested pathogens compared with ciprofloxacin ( Figure 5 a).…”
Section: Development Of Isatin Derivatives As Promising Therapeutic A...mentioning
confidence: 99%
“…In 2019, Gomaa et al [ 72 ] reported the synthesis and in vitro antimicrobial potential of N-aryl-N′-(2-oxoindolin-3-ylidene)-benzohydrazonamides ( 50a – j ) against B. cereus , S. aureus (Gram-positive), and E. coli , P. aeruginosa , and S. marcescens strains using the agar disc diffusion method. The research group emphasized that compounds 50b and 50d show the most promising activity towards S. aureus when compared to the standard drug ciprofloxacin, while the majority of analogues displayed broad-spectrum antibacterial potential against all tested pathogens compared with ciprofloxacin ( Figure 5 a).…”
Section: Development Of Isatin Derivatives As Promising Therapeutic A...mentioning
confidence: 99%
“…Based on bis-lactam design strategies, various novel electron-deficient building blocks for high-performance OSCs have been reported [8,9]. Isatin and its dicyanovinyl derivatives belong to this family, and they are good synthetic precursors of many natural products and promising n-type acceptor-donor-acceptor (A-D-A)-type OSCs due to their planar framework with two electron-withdrawing carbonyl groups [10][11][12]. In the past, various D-A-type dyad and triad architectures have been designed and synthesized, and their photophysical properties are largely influenced by how the dyad and triad systems are constructed (A-D, D-A-D, A-D-A, etc.).…”
Section: Introductionmentioning
confidence: 99%